Characterization and classification of major coconut growing soils in South Eastern Ghats of Tamil Nadu, India - Srinivasan, R.; Anil Kumar, K. S.; Chandrakala, M.; Niranjana, K. V.; Maddileti, N.; Hegde, Rajendra (Journal of Plantation Crops, 2021)
Six soil series representing major coconut growing soils of the Eastern Ghats in Krishnagiri district of Tamil Nadu State, India, were evolved from granite gneiss and alluvium parent materials. Characterization of different soil properties was done using a detailed soil survey at 1:10000 scale. The soils were neutral to moderately alkaline in reaction (7.31 to 9.19), non-saline, poor to moderately well-drained and moderately shallow (<75 cm) to very deep (>150 cm) in depth. The soils were sandy to clay in texture, sub-angular blocky to crumb in structure, dark reddish-brown to brown, very low to high in OC content (0.06 to 2.70%), low to medium in AWC (3.44 to 22.39%), low to high in CEC (4.70 to 54.0 cmol (p+) kg-1) and having high base saturation (77 to 100%). The soils also had sizable amounts of exchangeable sodium (4.29 to 33.46%), which was maximum in P5, P6 and P1, and high clay content in P5 and P2. The distribution of CaCO3 in different depths was found to be maximum in P4 and P1. The soil orders identified in the coconut area were Inceptisols, Entisols, Alfisols and Vertisols. Assessment of soil resources and identification of yield-limiting soils factors on coconut could be by way of better management and improved productivity.